Re-examining inequality persistence - Atanu Ghoshray; Mercedes Monfort; Javier Ordó\~nez (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
Although it is not a new phenomenon, in recent years inequality has moved to the top of the political agenda given the concern that will result in political instability and social resentment. Persistence in inequality can further undermine economic growth and development by hindering educational opportunities, human capital formation, and intergenerational mobility. The persistent nature of inequality stands as one of the most serious challenges for the global economy. This paper analyses inequality persistence for a sample of 60 countries from 1984 to 2015. The authors conclude that inequality is persistent and government redistribution polices through taxes and transfers did not significantly reduce inequality persistence.
Keywords: C23; D63; 330; inequality; persistence; Gini index; unit root; panel